Caring Behaviors of Nursing Students at Naresuan University - Wonghipthong, Kanokrat; Khom-u, Kuttalee; Danjittisiri, Kanokwan; Thiangtrong, Kamonrat; Thiangjan, Ninlawan; Thongdonngow, Waraporn; Thamicharoenthawon, Apapron; Kinzang, Yangden; Suwannakeeree, Wongduan (Thai Journal of Nursing, 2020)
This descriptive research study aimed to examine and compare the caring behaviors between the third and the fourth year of undergraduate nursing students at Naresuan University. A sample of 146 nursing students was randomly selected. The research tool was the caring behavior questionnaire, developed based on Watson’s Theory of Human Caring. The Cronbach’s alpha coefficient of the questionnaire was 0.91. Data were analyzed by descriptive statistics, t-test and Mann-Whitney U test. The results were found that the caring behaviors of nursing students were at the high level (M = 2.57, SD = 0.39). Caring behaviors of the fourth year nursing students were significantly higher than those in the third year at p < .05.